Advantages and Current Issues of Blockchain Use in Microgrids - Konashevych, O.I. (Электронное моделирование, 2016)
This paper provides the analysis of the blockchain use in microgrids. The analysis is given from the hypothesis that with the help of IT instruments, self-governed decentralized organizations based on blockchain technology will take and perform public functions traditionally performed by central authorities and corporations in order to organize their relations within the microgrids. Представлен анализ использования технологии blockchain в энергетических микросетях на основе гипотезы о том, что с помощью IТ-инструментов самоуправляемые децентрализованные организации будут выполнять публичные функции, традиционно выполняемые центральными органами и компаниями для организации отношений в рамках работы микросетей.